IMPLEMENTASI SIMPATIKA DAN DAMPAKNYA PADA PROFESIONALISME GURU PAI - Jannah, Rifqotul; Ruslan (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2026)
This study examines the implementation of SIMPATIKA (Management Information System for Educators and Education Personnel) and its relevance to the professionalism of Islamic Education (PAI) teachers at Nurul Amal Islamic Educational Institution. The study is motivated by the gap between the ideal function of SIMPATIKA as a strategic educational management tool and its actual implementation at the institutional level. The purpose of this research is to analyze the implementation of SIMPATIKA, its relevance to teacher professionalism, and its supporting and inhibiting factors. This research employs a qualitative approach using the Participatory Action Research (PAR) method. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results show that the implementation of SIMPATIKA is still administrative and operator-centered, and has not been supported by strategic planning. The system contributes to improving discipline, accountability, and moral values such as honesty and responsibility among teachers, but it has not been optimal in enhancing overall teacher professionalism. Supporting factors include leadership commitment and the role of operators, while inhibiting factors include limited technological competence among teachers and technical system constraints. SIMPATIKA functions effectively as an administrative control tool but has not yet been optimal as an instrument for developing teacher professionalism.